2013
DOI: 10.1037/a0031887
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental frequency during couple conflict: An analysis of physiological, behavioral, and sex-linked information encoded in vocal expression.

Abstract: The human voice is one of the sounds most frequently experienced by human beings. During couple conflict, higher fundamental frequency (f0), a physical property of human speech, has been linked to an increased risk of divorce, less beneficial response to couple therapy, and higher levels of dysfunctional communication behavior. F0 is generally considered to be a measure of emotional arousal, but it is not currently clear whether this interpretation is appropriate for understanding spouses' f0 during couple int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 51 publications
(54 reference statements)
1
86
1
8
Order By: Relevance
“…Mean f 0 is highly correlated with perceived pitch (up to r = .9) and is widely interpreted as a measure of vocally encoded emotional arousal (Juslin & Scherer, 2005; Kappas et al, 1991; Russell, Bachorowski, & FernĂĄndez-Dols, 2003). Vocally encoded emotional arousal refers to the degree of emotional activation conveyed by the voice (e.g., high = excited, angry, or nervous; low = bored, calm, or content), and higher levels of f 0 have been linked to higher levels of physiological (e.g., higher heart rate, higher systolic and diastolic blood pressure, and greater cortisol output; Scherer, 1989; Weusthoff, Baucom, & Hahlweg, 2013) and self-reported emotional arousal (e.g., Baucom et al, 2012). A series of studies indicate that f 0 converges as dyads converse (see Gregory, 1990; Gregory, Webster, & Huang, 1990).…”
Section: Empathy and Synchronymentioning
confidence: 99%
“…Mean f 0 is highly correlated with perceived pitch (up to r = .9) and is widely interpreted as a measure of vocally encoded emotional arousal (Juslin & Scherer, 2005; Kappas et al, 1991; Russell, Bachorowski, & FernĂĄndez-Dols, 2003). Vocally encoded emotional arousal refers to the degree of emotional activation conveyed by the voice (e.g., high = excited, angry, or nervous; low = bored, calm, or content), and higher levels of f 0 have been linked to higher levels of physiological (e.g., higher heart rate, higher systolic and diastolic blood pressure, and greater cortisol output; Scherer, 1989; Weusthoff, Baucom, & Hahlweg, 2013) and self-reported emotional arousal (e.g., Baucom et al, 2012). A series of studies indicate that f 0 converges as dyads converse (see Gregory, 1990; Gregory, Webster, & Huang, 1990).…”
Section: Empathy and Synchronymentioning
confidence: 99%
“…Computing f 0 is an ideal method for measuring emotional arousal because it is related to spouse’s physiological and subjective experiences of emotional arousal (e.g., Weusthoff et al, 2013), conveys information about one spouse’s internal emotional state, is related to maladaptive communication behaviors (e.g., B. Baucom et al, 2011), is related to couple therapy outcomes (e.g., B.…”
mentioning
confidence: 99%
“…From a methodological perspective, this study adds to a growing literature on vocally encoded emotional arousal in couples, although prior studies were not focused on couples in which one partner has a psychological disorder (Baucom, Dickenson, et al, 2015; Baucom, Weusthoff, et al, 2012; Fischer, Baucom, et al, 2015; Weusthoff et al, 2013). However, these studies collectively suggest that vocally encoded arousal plays an important role for our understanding of couple interactions in a variety of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed discussions of vocal measures of arousal, including fundamental frequency (f 0 ), and its empirical status (Bachorowski & Owren, 1995; Juslin & Scherer, 2005) as well as the utility of f 0 in couples research (Weusthoff, Baucom, & Hahlweg, 2013) are available elsewhere. Broadly, several studies demonstrated that overall levels of f 0 (Baucom et al, 2011; Baucom, Weusthoff, Atkins, & Hahlweg, 2012; Fischer, Baucom, et al, 2015) as well as within-conversation changes (Baucom, Dickenson, et al, 2015; Baucom, Sheng, et al, 2015) are associated with cross-sectional and longitudinal relationship outcomes.…”
mentioning
confidence: 99%